Alpha4 beta7 integrin controls Th17 cell trafficking in the spinal cord leptomeninges during experimental autoimmune encephalomyelitis - Rossi, Barbara; Dusi, Silvia; Angelini, Gabriele; Bani, Alessandro; Lopez, Nicola; Della Bianca, Vittorina; Pietronigro, Enrica Caterina; Zenaro, Elena; Zocco, Carlotta; Constantin, Gabriela (Frontiers in Immunology, 2023)
Th1 and Th17 cell migration into the central nervous system (CNS) is a fundamental process in the pathogenesis of experimental autoimmune encephalomyelitis (EAE), the animal model of multiple sclerosis (MS). Particularly, leptomeningeal vessels of the subarachnoid space (SAS) constitute a central route for T cell entry into the CNS during EAE. Once migrated into the SAS, T cells show an active motility behavior, which is a prerequisite for cell-cell communication, in situ reactivation and neuroinflammation. However, the molecular mechanisms selectively controlling Th1 and Th17 cell trafficking in the inflamed leptomeninges are not well understood. By using epifluorescence intravital microscopy, we obtained results showing that myelin-specific Th1 and Th17 cells have different intravascular adhesion capacity depending on the disease phase, with Th17 cells being more adhesive at disease peak. Inhibition of L2 integrin selectively blocked Th1 cell adhesion, but had no effect on Th17 rolling and arrest capacity during all disease phases, suggesting that distinct adhesion mechanisms control the migration of key T cell populations involved in EAE induction. Blockade of 4 integrins affected myelin-specific Th1 cell rolling and arrest, but only selectively altered intravascular arrest of Th17 cells. Notably, selective 47 integrin blockade inhibited Th17 cell arrest without interfering with intravascular Th1 cell adhesion, suggesting that 47 integrin is predominantly involved in Th17 cell migration into the inflamed leptomeninges in EAE mice. Two-photon microscopy experiments showed that blockade of 4 integrin chain or 47 integrin selectively inhibited the locomotion of extravasated antigen-specific Th17 cells in the SAS, but had no effect on Th1 cell intratissue dynamics, further pointing to 47 integrin as key molecule in Th17 cell trafficking during EAE development. Finally, therapeutic inhibition of 47 integrin at disease onset by intrathecal injection of a blocking antibody attenuated clinical severity and reduced neuroinflammation, further demonstrating a crucial role for 47 integrin in driving Th17 cell-mediated disease pathogenesis. Altogether, our data suggest that a better knowledge of the molecular mechanisms controlling myelin-specific Th1 and Th17 cell trafficking during EAE delevopment may help to identify new therapeutic strategies for CNS inflammatory and demyelinating diseases.